Hubungan Tingkat Pengetahuan tentang HIV/AIDS dengan Sikap Pencegahan HIV/AIDS pada Remaja - I Ketut Andika Priastana; Hendra Sugiarto (Indonesian Journal of Health Research, 2018)
Introduction. Human Immunodeficiency Virus (HIV) is a virus that attacks the human immune system and Acquired immunodeficiency Syndrome (AIDS) is a collection of symptoms of disease caused by HIV. UNICEF stated that the number of deaths among adolescents due to HIV/AIDS has increased. In Indonesia, cases of HIV/AIDS have begun to attack adolescents, one of the causes of which is a lack of knowledge about HIV/AIDS. This study aims to determine the relationship between the level of knowledge about HIV/AIDS with the prevention attitude against HIV/AIDS in adolescents in Jembrana, Bali, Indonesia. Methods. The research design used was cross sectional, random sampling technique with a sample of 82 people. The statistical analysis used was Chi square test with a significance level of 5%. Results. The results showed that the majority of respondents in the category of sufficient knowledge, namely as many as 53.7% and most had an agreeing attitude towards the prevention of HIV/AIDS as many as 65.9%. The results of the analysis of the Chi square test showed that the relationship between the level of knowledge about HIV/AIDS and the attitude of prevention of HIV/AIDS in adolescents showed p value = 0.001 (p value <0.05). Conclusion. This study found that there was a correlation between the level of knowledge about HIV/AIDS and the attitude of preventing HIV/AIDS in adolescents. Teenagers can improve their knowledge more optimally so that they are more vigilant and supportive of HIV/AIDS prevention.